[3+2] Cycloaddition of Trifluoromethylated N‐Acylhydrazones with Azomethine Ylides: Synthesis of Trifluoromethylated Imidazolidines. Issue 7 (20th April 2020) - Zhao, Fangxia; Wang, Ke‐Hu; Wen, Lan; Zhao, Zhuanxia; Hu, Yongqin; Xu, Weigang; Huang, Danfeng; Su, Yingpeng; Wang, Junjiao; Hu, Yulai
Abstract: Trifluoromethylated N‐ acylhydrazones are used as dipolarophiles to perform 1, 3‐dipolar cycloadditions with azomethine ylides to afford trifluoromethylated 1, 2, 4, 5‐tetrasubstituted imidazolidines in good yields under mild conditions. The role switch of the trifluoromethylated N ‐acylhydrazones demonstrates that they are versatile trifluoromethyl building blocks for CF3 ‐containing heterocycles. Abstract : Trifluoromethylated N ‐acylhydrazones are used as dipolarophiles to perform 1, 3‐dipolar cycloaddition with azomethine ylides to afford trifluoromethylated 1, 2, 4, 5‐tetrasubstituted imidazolidines in good yields under mild conditions.